Metal Clusters and Nanoalloys : From Modeling to Applications. - Mariscal, Marcelo Mario (Nanostructure science and technology., 2013)
Metallic nanoparticles hold promise for their potential applications in a wide array of disciplines ranging from materials science to medicine. This book brings the power of theoretical methods to an audience of experimentalists, and explicates the simulation of metallic clusters and nanoparticles. It begins with a summary of the current state of research on metallic nanoparticles, then moves on to the current state of the art in theory of metallic nanoparticldes, and then explains why and how these tools help experimentalists. Contributions are provided by renowned experts in the field from across the world.